Conceptual framework and guidelines for the establishment of district-based information systems - Rodrigues, Roberto (PAHO BridgetownBB, 1995)
Aims to provide health professionals with a working knowledge about the role and components of information systems as they apply to health and health care delivery in general and to local or District Health systems in particular.